Improving Graduate Quality in Vocational High Schools through Pesantren Curriculum Integration: A Vocational Approach - Afifah Hidayati; Farihin Nur; Amin Haedari; Abdul Karim; Jalaludin; Upid Abdul Mupid (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to examine the management of curriculum integration in pesantren-based vocational high schools (SMK) and evaluate its effectiveness in improving the quality of graduates. The research was conducted at SMK Khas Kempek Cirebon using a qualitative interpretive approach. Data were collected through participatory observation, in-depth interviews, and curriculum documentation, with validation achieved through triangulation. Curriculum integration involved planning with input from the foundation as the primary stakeholder and the design of a pesantren-based learning program supported by a SWOT analysis of national education standards. The findings reveal that curriculum integration was systematically managed through a combination of general and religious instruction, supervised by the principal and the structural team. However, the evaluation conducted was still descriptive and lacked quantitative indicators to measure graduate improvement. Student participation in pesantren-based learning activities yielded positive results, with more than 70% of final-year students undertaking internships at pesantren-run institutions. Additionally, more than 80% of students demonstrated competencies in religious activities such as Quran memorization and funeral rites. This study was limited to a single institution, which may restrict the generalizability of the findings. The research did not investigate the long-term outcomes of curriculum integration or the impact of socio-cultural factors on student success. Future research could expand this study by including multiple pesantren-based SMKs to provide a broader perspective. This study recommends the development of a graduate-based evaluation system, continuous teacher training, and strengthening strategic collaboration between pesantren and SMKs in educational planning. The contribution of this study is to develop vocational education models that are more relevant to labor market needs while emphasizing moral and spiritual education.